Sharia-Based Marketing Strategy For Umrah Services At Al-Bahjah Haji dan Umroh - Bahri, Muhammad; Saechu, Muhammad; Kurniawan, Heru (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study aims to analyze the marketing strategies implemented by Al-Bahjah Hajj & Umrah, examine their conformity with Sharia marketing principles, and identify the challenges encountered in their implementation. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that Al-Bahjah Hajj & Umrah integrates modern marketing concepts with Islamic values through digital marketing, educational and da’wah-based promotion, partnership development, excellent service, customer loyalty programs, and its flagship Munajat Kubro program. These strategies reflect the application of Marketing 4.0 through digital technology and Marketing 5.0 through customer-oriented services. The marketing practices also demonstrate compliance with Sharia principles, including ṣidq (honesty), amanah (trustworthiness), transparency, maslahah (public benefit), and the avoidance of gharar (uncertainty), as evidenced by transparent information disclosure, supervised promotional content, and the integration of Al-Bahjah’s Manhajiah values into marketing activities. However, the company faces several challenges, including dependence on Buya Yahya’s figure, competition from illegal travel agencies, the rise of backpacker Umrah, regulatory changes in Indonesia and Saudi Arabia, rapid digital marketing developments, and the need to improve human resource quality. To address these challenges, Al-Bahjah Hajj & Umrah continues to strengthen service quality, public education, digital marketing innovation, and human resource development to sustain pilgrims’ trust and loyalty.